2021
DOI: 10.1021/acsami.1c07019
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Electrode Properties for High-Performance Ni-Rich Li-Ion Batteries

Abstract: The microstructure of the electrodes in lithium-ion batteries (LIBs) strongly affects their gravimetric and volumetric energy and power as well as their cycle life. Especially, the effect of the microstructure in the case of next-generation Ni-rich cathode materials has not yet been investigated. A comprehensive understanding of the calendering process is therefore necessary to find an optimal level of the electrode microstructure that can enhance lithium-ion transportation, minimize plastic deformation, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The change in the peak intensity in d Q /d V is more in NMC-CB-MLG-G at 3.5 and 3.7 V. The quantity of electrolyte added and soaking time for the electrode wetting are the same in both cells. The % electrolyte uptake is calculated by following the ref . The % electrolyte uptake (EU) is more in NMC-CB-MLG electrode (26%) than NMC-CB electrode (21%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in the peak intensity in d Q /d V is more in NMC-CB-MLG-G at 3.5 and 3.7 V. The quantity of electrolyte added and soaking time for the electrode wetting are the same in both cells. The % electrolyte uptake is calculated by following the ref . The % electrolyte uptake (EU) is more in NMC-CB-MLG electrode (26%) than NMC-CB electrode (21%).…”
Section: Resultsmentioning
confidence: 99%
“…CAs will also influence tortuosity and electrolyte uptake, in addition to the e – and Li + transport. A better understanding of these effects can be investigated by multilayer pouch cells. , However, only a few studies explored the usage of alternative CAs in the pouch cell format. Fang et al tested graphene as a CA using a prototype pouch cell with an estimated capacity of 10 Ah .…”
Section: Introductionmentioning
confidence: 99%
“…[193] Compaction of the cathodes via calendering can improve the electronic percolation network and volumetric energy density, however, for NCA, over-compaction can destroy the mechanical properties, facilitate particle cracking and restrict electrolyte wetting. [193] It is vital to optimize the calendering approach for this material. Lu et al [194] investigated the impact of calendering on LiNi 0.8 Co 0.15 Al 0.05 O 2 (NCA) cathodes, prepared with Gr, CB and PVDF, with varying thicknesses and demonstrated that improved coating uniformity could be achieved after calendering.…”
Section: Lithium-nickel-aluminum-oxidesmentioning
confidence: 99%
“…[ 192 ] However, Ni‐rich cathodes can be subject to extreme capacity fading owing to CAM particle cracking and breakage during long‐term cycling. [ 193 ] Compaction of the cathodes via calendering can improve the electronic percolation network and volumetric energy density, however, for NCA, over‐compaction can destroy the mechanical properties, facilitate particle cracking and restrict electrolyte wetting. [ 193 ] It is vital to optimize the calendering approach for this material.…”
Section: Performance Of Calendered Lib Electrodesmentioning
confidence: 99%
See 1 more Smart Citation